2016
DOI: 10.1093/mnras/stw718
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of extreme [O iii] λ5007 Å outflows in high-redshift red quasars

Abstract: Black hole feedback is now a standard component of galaxy formation models. These models predict that the impact of black hole activity on its host galaxy likely peaked at z = 2−3, the epoch of strongest star formation activity and black hole accretion activity in the Universe. We used XShooter on the Very Large Telescope to measure rest-frame optical spectra of four z ∼ 2.5 extremely red quasars with infrared luminosities ∼ 10 47 erg s −1 . We present the discovery of very broad (full width at half max= 2600 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
277
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 218 publications
(306 citation statements)
references
References 161 publications
(210 reference statements)
28
277
1
Order By: Relevance
“…The comparison between the energy of the inner UFOs and that of the large-scale molecular outflows suggest that AGN outflows are closer to the energy-driven limit than to the momentum-driven limit (see Section 2); that is, the UFOs are able to inflate a bubble of hot gas that does not cool efficiently and whose thermal pressure can push layers of colder gas to large distances. Very recently, further support for the existence of hot gas bubbles around AGN came from the detection of the thermal Sunyaev-Zeldovich effect on the stacked far-infrared spectra of large populations of z ∼ 2 QSOs (Ruan et al 2015;Crichton et al 2016) AGN-driven outflows are obviously best studied in nearby objects, but they are observed in AGN at all redshifts (Brusa et al 2015;Zakamska et al 2016), even beyond redshift 6 (Maiolino et al 2012), i.e. in the most distant QSOs known.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison between the energy of the inner UFOs and that of the large-scale molecular outflows suggest that AGN outflows are closer to the energy-driven limit than to the momentum-driven limit (see Section 2); that is, the UFOs are able to inflate a bubble of hot gas that does not cool efficiently and whose thermal pressure can push layers of colder gas to large distances. Very recently, further support for the existence of hot gas bubbles around AGN came from the detection of the thermal Sunyaev-Zeldovich effect on the stacked far-infrared spectra of large populations of z ∼ 2 QSOs (Ruan et al 2015;Crichton et al 2016) AGN-driven outflows are obviously best studied in nearby objects, but they are observed in AGN at all redshifts (Brusa et al 2015;Zakamska et al 2016), even beyond redshift 6 (Maiolino et al 2012), i.e. in the most distant QSOs known.…”
Section: Introductionmentioning
confidence: 99%
“…Although it is difficult to constrain the opening angle of UFOs, in the powerful local quasi-stellar object (QSO) PDS456 the remarkable P Cygni profile of the FeXXVI Kα line indicates the presence of a subrelativistic wind expanding almost spherically. On much larger scales (∼kpc), outflows of less ionized gas have been traced through observations of asymmetric emission lines in the optical regime, such as the [OIII]5007Å line (Brusa et al 2015;Harrison et al 2016;Shen 2016;Zakamska et al 2016). Outflows of neutral atomic and molecular gas have also been observed.…”
Section: Introductionmentioning
confidence: 99%
“…Our compilation include AGN which are known to show wind signatures in absorption (Edmonds et al 2011;Rupke et al 2005a;Krug et al 2010;Borguet et al 2012;Arav et al 2013;Borguet et al 2013;Rupke & Veilleux 2013;Chamberlain & Arav 2015), in ionized gas emission (Liu et al 2013;Rupke & Veilleux 2013;Harrison et al 2014Harrison et al , 2016McElroy et al 2015;Carniani et al 2015;Zakamska et al 2016) and in molecular gas (Combes et al 2013;Cicone et al 2014;Sun et al 2014;García-Burillo et al 2015;Tombesi et al 2015) All the absorption line and molecular gas based kinetic wind power measurements are taken directly from values published in the literature, while all the emission-line based the wind power measurements except those taken from Rupke & Veilleux (2013) are based on our calculations. Where the wind power measurements for the ionized gas are not available, we estimate them following the standard methods and assumptions (e.g., Nesvadba et al 2006;Harrison et al 2014;Zakamska et al 2016). Using the equation below, the wind power for all ionized gas measurements are estimated from nebular emission lines assuming a wind radius of 3 kpc, electron density of 100 cm −3 and the velocity-width is 1.3 times the initial wind velocity, W 80 = 1.3v 0 (for a spherically symmetric and constant velocity wind).…”
Section: Discussionmentioning
confidence: 99%
“…They are potentially one of the most important pieces of feedback from AGNs and may play a crucial role in galaxy formation and evolution, connecting the central supermassive black holes (SMBHs) to their host galaxies and regulating their coevolution (e.g., Granato et al 2004;Scannapieco & Oh 2004;Hopkins et al 2008). Previous works suggested that the AGN outflows can reach from the small scale (at or outside of the broad emission line region [BELR]; e.g., Zhang et al 2015c;Williams et al 2016) to the intermediate scale (the dusty torus; e.g., Leighly et al 2015;Zhang et al 2015b;Shi et al 2016), the large scale (the inner narrow emission line region [NELR]; e.g., Komossa et al 2008;Crenshaw et al 2010;Ji et al 2015;Liu et al 2016), and even the entire host galaxy of the quasar (e.g., Zakamska et al 2016). There is general agreement that there has to be a radial component of motion and some opacity source; however, questions regarding the origins, whether homologous or not, and the properties themselves of the blueshifted-ELs and BALs remain interesting subjects of debate.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, the broad and narrow blueshifted-ELs (BBELs and BNELs) are generally mixed with the normal broad or narrow lines. The existence of the blueshifted-ELs is expressed by the differences in the line profile (e.g., asymmetry, width, peak, and/or velocity centroid) with respect to the lines emitting from the BELR and NELR (e.g., Gaskell 1982;Wilkes 1984;Crenshaw 1986;Marziani et al 1996Marziani et al , 2013Richards et al 2002;Zamanov et al 2002;Boroson 2005;Snedden & Gaskell 2007;Crenshaw et al 2010;Rafiee et al 2016), and the strength measurement relies on the blueshift and asymmetry index for C IV , or the distinguishing of the blueshifted wings for [ ] O III λ5007 (e.g., Komossa et al 2008;Zhang et al 2011;Zakamska et al 2016) and for Hβ and Mg II (e.g., Marziani et al 2013).…”
Section: Introductionmentioning
confidence: 99%